Manufacturing without the firm: Challenges for the maker movement in three U.S. cities. (May 2018) - Doussard, Marc; Schrock, Greg; Wolf-Powers, Laura; Eisenburger, Max; Marotta, Stephen
Participants in the U.S. maker movement generate market-worthy consumer goods from the bare bones of novel ideas and simple production equipment. For cities and policymakers, making thus represents the opportunity to develop new manufacturing industries and employment. For makers to transform themselves into large-volume producers, however, they must negotiate significant financing, production and distribution barriers without recourse to the capabilities of the large manufacturing firm. Drawing on 137 interviews with makers and maker-supporting organizations, we call attention to the challenges of "manufacturing without the firm, " as well as the extent to which the localized institutional ecosystems in which makers are embedded may help them circumvent these challenges. Our findings indicate that the maker movement's generative prospects rest on these firms' ability to negotiate problems of production and markets that have beset clusters of small firms for many decades.